Amino Acid Transporter SLC6A14 (ATB0,+) – A Target in Combined Anti-cancer Therapy - Nałęcz, Katarzyna A. (Frontiers in Cell and Developmental Biology, 2020)
Cancer cells are characterized by quick growth and proliferation, demanding constant supply of various nutrients. Several plasma membrane transporters delivering such compounds are upregulated in cancer. Solute carrier family 6 member 14 (SLC6A14), known as amino acid transporter B0,+ (ATB0,+) transports all amino acids with exception of the acidic ones: aspartate and glutamate. Its malfunctioning is correlated with several pathological states and it is upregulated in solid tumors. The high expression of SLC6A14 is prognostic and unfavorable in pancreatic cancer, while in breast cancer it is expressed in estrogen receptor positive cells. As many plasma membrane transporters it resides in endoplasmic reticulum (ER) membrane after translation before further trafficking through Golgi to the cell surface. Transporter exit from ER is strictly controlled. The proper folding of SLC6A14 was shown to be controlled from the cytoplasmic side by heat shock proteins, further exit from ER and formation of coatomer II (COPII) coated vesicles depends on specific interaction with COPII cargo-recognizing subunit SEC24C, phosphorylated by kinase AKT. Inhibition of heat shock proteins, known to be upregulated in cancer, directs SLC6A14 to degradation. Targeting proteins regulating SLC6A14 trafficking is proposed as an additional pharmacological treatment of cancer.